Working Capital Management in Selected Indian Steel Companies - Chandra, H.; Selvaraj, A. (Indian Journal of Finance, 2012)
Working capital is the backbone of an organization. It refers to a portion of the total fund which finances the day to day working expenses during the operating cycle. Management of working capital is one of the most important functions of corporate management. It is rightly said, "Inadequate working capital is advantageous, whereas redundant working capital is a criminal waste". As a large manufacturing industry, working capital management in the steel industry involves a large portion of the company’s total assets. The optimum working capital ensures the success of the business, while its inefficient management will lead to the down fall of the company. Hence, this paper analyses the working capital management of selected steel companies in India. Further, to measure the effective utilization of the working capital, Operating Cycle and Cash Conversion Cycle were used. To measure the determinants of Cash Conversion Cycle, the Kieschnick model has been used. Finally, it was concluded that the size of a company plays a vital role in determining the efficiency of its working capital management.